Improved Ionization Energies for the Two Isomers of Phenylpropargyl Radical. Issue 16 (8th August 2014) - Holzmeier, Fabian; Lang, Melanie; Hemberger, Patrick; Fischer, Ingo
Abstract The ionization of two resonantly stabilized radicals, namely 1‐phenylpropargyl (1PPR) and 3‐phenylpropargyl (3PPR) are reinvestigated applying vacuum ultraviolet synchrotron radiation and threshold photoelectron spectroscopy. Ionization energies of 7.24±0.02 and 7.25±0.01 eV are obtained for 1 and 3PPR respectively, which compare well with ab initio calculations. The quality of the spectra are significantly improved mostly due to the application of a new high‐photon‐flux grating available at the VUV‐beamline of Swiss Light Source. Resolved vibrational features are assigned according to a Franck–Condon approach.